Attitudes in Social Media Affect Learning Motivation: Evidence from Java, Indonesia: Sikap di Media Sosial berpengaruh Terhadap Motivasi Belajar: Bukti dari Jawa, Indonesia - Ignatius Ario Sumbogo (Academia Open, 2022)
The development of student learning motivation is the very dynamic, main task of teachers, particularly in the era of the digital revolution 4.0. Millennial students have been immersed into digital technology, by which learning instruments must also be adjusted, including the competencies, services and attitudes of educators. This study is an attempt to determine the strong influence of social media engagement, competence, service, and teacher attitudes on the learning motivation of high school students. This research was conducted using a field research method with a quantitative approach among 50 students from 22 institutions in 3 provinces, DKI Jakarta, West Java and Central Java. The sampling method is non-probability sampling with purposive sampling type, using a single criteria that is high school students, and data processing techniques is multiple linear regression. The results of the research show that teachers’ social media engagement has a significant effect on learning motivation, teachers’ competence has a significant effect on learning motivation, teacher’ attitude has a significant effect on learning motivation, and teachers’ service has no significant effect on learning motivation. This research is expected to help developing the enthusiasm of high school teachers in improving several aspects to become a favorite figure among students which has impact on the effectivity and efficiency of teaching and learning process.